PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP ORIENTASI KEWIRAUSAHAAN (STUDI KASUS PADA UMKM KULINER JAKARTA BARAT) - Oktafalia Marisa; Yustinus Yuniarto (Jurnal Bina Manajemen, 2018)
Micro and Medium Entreprese growth nowadays need some effective marketing program in order to expand the market. The use of social media as one of the marketing tools now becomes very critical and important. This research tried to indentify the impact of social media to micro medium entreprise in culinary sector at west Jakarta, Tanjung Duren. This is one of quantitative descriptive research about UMKM that utilize social media as their marketing tools. In this research there are two variables that would like to be observed, entrepreneurship oritentation as dependent variable and social media impact as independent variable. Simple linear regression was used as analytic tool to test some hypothesis that would like to be tested in this research. Finding in this research conclude social media has an impact to entrepreneurship orientation base on t and f test that has been calculated.